2019
DOI: 10.1055/s-0039-1695705
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Resident Involvement on Surgical Outcomes following Anterior Cruciate Ligament Reconstruction

Abstract: Hands-on participation in the operating room (OR) is an integral component of surgical resident training. However, the implications of resident involvement in many orthopaedic procedures are not well defined. This study aims to assess the effect of resident involvement on short-term outcomes following anterior cruciate ligament reconstruction (ACLR). The National Surgical Quality Improvement Program (NSQIP) database was queried to identify all patients who underwent ACLR from 2005 to 2012. Demographic variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Cvetonovich et al performed a propensity score analysis for patients undergoing total shoulder arthroplasty and reported no evidence of increased 30-day complications or mortality with associated resident involvement. 19 More recently, Lebedeva et al 15 confirmed these findings of low complication rates with no impact of resident involvement in patients undergoing anterior cruciate ligament reconstruction.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Cvetonovich et al performed a propensity score analysis for patients undergoing total shoulder arthroplasty and reported no evidence of increased 30-day complications or mortality with associated resident involvement. 19 More recently, Lebedeva et al 15 confirmed these findings of low complication rates with no impact of resident involvement in patients undergoing anterior cruciate ligament reconstruction.…”
Section: Discussionmentioning
confidence: 83%
“…The impact of resident involvement in surgical procedures has been explored in various surgical and orthopaedic procedures. 15 16 17 18 19 20 21 22 Haughom et al 21 performed a retrospective analysis on the impact of residents involved in total hip arthroplasty 20 and total knee arthroplasty cases. These two studies did not identify resident involvement as a risk factor for 30-day morbidity or mortality in these selected cases.…”
Section: Discussionmentioning
confidence: 99%
“…In a myriad of orthopedic studies, resident involvement was not linked to an increase in morbidity or mortality. 13,17,18,[20][21][22]26 These findings are especially promising, since it is thought that residents are more likely to be involved in more rare and complex "teaching cases". 9,24 Hip arthroscopy (HA) is a relatively recent procedure that has seen an explosion in case volume in recent years, 34 yet there are currently few studies examining resident participation in hip cases and no studies focusing on HA specifically.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 , 12 Current opinion is conflicted as to whether or not resident involvement is a detriment to surgical outcomes, and results vary by specialty. Some studies have demonstrated no significant differences in outcomes with versus without residents, 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 while others have argued for the protective effects of resident involvement, 13 , 19 , 23 , 24 , 25 , 26 and still a third group has found that resident presence is accompanied by an increase in morbidity and/or mortality. 8 , 24 , 27 , 28 , 29 Even within studies, there is conflicting overlap where, for example, morbidity rates increase, but mortality rates decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Since resident education is crucial in producing highly skilled and well-trained future health-care providers, residency programs must optimize patient safety and surgical outcomes, while also providing direct “hands-on” resident training efficiently. Several studies in various surgical specialties [ [9] , [10] , [11] , [12] ], including orthopaedics [ 1 , 2 , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ], have compared cost, outcomes, and adverse effects between teaching and nonteaching hospitals but present conflicting data [ 1 , 2 , 14 , 15 , [18] , [19] , [20] ]. Most of these studies utilized the American College of Surgeons National Surgical Quality Improvement Program database [ 21 ], which lacks specific details and consistency pertaining to residents’ experience and degree of participation in procedures [ 12 , 16 , 17 , 22 ].…”
Section: Introductionmentioning
confidence: 99%